La libertad de prensa en la posrevolución. El amparo al Diario de Yucatán (1931-1933) (Tzintzun, Revista de Estudios Históricos, 2016)
he court decision in favor of the Diario de Yucatán is one of the most importantcases concerning freedom of the press in the irst half of twentiethcenturyMexico. Although the paper might have been shuttered for its conservativetone, publishing articles against the revolutionary government ofBartolomé García Correa, who was close to ex-president Plutarco Elías Callesand the Partido Nacional Revolucionario (pnr), it received legal approval tokeep printing. he judicial process of Diario de Yucatán demonstrates increasingstrength of the judicial system and the diferences at several levels ofjustice as Mexico recovered from war.
Keywords: freedom of press; federal justice; Legal Protection; Mexican Revolution; Mexican Presidentialism